Variations in leisure activity preferences based on ethnicity of urban park users / Amelia Ahmad - Ahmad, Amelia (Institute of Graduate Studies, UiTM, 2016)
Urban parks provide excellent setting for urbanites to pursue leisure time activities. In an ethnically diverse country as Malaysia, park designers, planners and managers are presented with challenges to ensure the promotion of equal access as well as to meet the needs and expectations of the different ethnic groups. Many urban parks failed to incorporate the socio-cultural and behavioural characteristics of the varied park users, focusing mainly on the material and physical aspects of their designs. The concern for ethnic variations in leisure activity preferences occurs due to the fact that the recreation behaviours of some groups may have caused them to be marginalised in their recreation experiences, or lead to facility damage and resource degradation, and also little is known on how ethnic background of recreational users shaped their recreational experiences. This research aims to examine the variations in leisure activity preferences of urban park users across three main groups, that is, Malays, Chinese and Indians. The leisure activity preferences examined includes park usage patterns and participation; social composition; and settings. Two urban parks located in Perak were studied, both being, Taiping Lake Garden (TLG) and Padang Polo, Ipoh (PPI). The data for this study was collected using two methods, that is, observation and survey; and data were then analysed using descriptive statistics…